Kompetensi Dosen dalam Merancang Evaluasi Pembelajaran Pendidikan Agama Islam: Analisis Dokumen RPS dan Soal UAS - Ahmad Yunus Mokoginta Harahap; Syaukani; Nurmawati; Aisyah Aminy; Misnan (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study analyzes lecturers’ competence in designing learning evaluation for Islamic Religious Education through an examination of semester learning plans (RPS) and final examination (UAS) questions. A mixed-method approach with a sequential explanatory design was employed. Quantitative analysis measured the fulfillment of seven indicators of evaluation-design competence, while qualitative content analysis examined alignment with learning outcomes, higher-order thinking skills (HOTS), authentic assessment, and the principles of Merdeka Belajar. The data comprised Two RPS for the Islamic Education Curriculum Development course and UAS instruments from the Islamic Education Learning Strategies and Islamic Education Learning Resources and Media Development courses. The findings indicate that lecturers’ competence was in the very high category, with an average indicator fulfillment of 87.4%. The evaluation instruments were generally aligned with course learning outcomes, emphasized analytical, evaluative, and creative thinking, incorporated authentic professional tasks, and supported student-centered learning. Nevertheless, detailed scoring rubrics, systematic affective-domain assessment, and digital assessment practices remained limited. These findings highlight the need to strengthen assessment literacy and technology-supported evaluation to improve the objectivity, comprehensiveness, and adaptability of assessment in Islamic higher education.